2016
DOI: 10.14712/23361964.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, parasitoids and cyclic appearance of Russian wheat aphid Diuraphis noxia (Mordvilko, 1913) (Hemiptera, Aphididae) in Algeria

Abstract: This information on the Russian wheat aphid Diuraphis noxia (Hemiptera, Sternorrhyncha, Aphididae) in those regions of Algeria where cereals are grown is based on a nineteen year study. This revealed that this aphid is widely distributed in the high plateaus and interior plains with semi-arid climates. The mummies of this aphid found among its colonies were collected and 4 parasitoids (Hymenoptera, Braconidae, Aphidiinae) where identified. These were Diaeretiella rapae (M'Intosh), Aphidius matricariae (Haliday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…This association was also mentioned in other regions in Algeria (Chehma and Laamari 2014;Tahar Chaouche and Laamari 2015;. Laamari et al (2016) noted that this species was found at several locations in all cereal crops, and it was considered as the most important parasitoid of the Russian wheat aphid Diuraphis noxia (Kurdjumov).…”
Section: Tri-trophic Relationships: Parasitoids-aphids-plantssupporting
confidence: 62%
“…This association was also mentioned in other regions in Algeria (Chehma and Laamari 2014;Tahar Chaouche and Laamari 2015;. Laamari et al (2016) noted that this species was found at several locations in all cereal crops, and it was considered as the most important parasitoid of the Russian wheat aphid Diuraphis noxia (Kurdjumov).…”
Section: Tri-trophic Relationships: Parasitoids-aphids-plantssupporting
confidence: 62%
“…Diuraphis noxia (Kurdjumov) (Starý et al 2000;Uysal et al 2004;Laamari et al , 2016; Metopolophium dirhodum (Walker) (Rakhshani et al 2008a(Rakhshani et al , 2008b; Rhopalosiphum maidis (Fitch) (Ghanim & El-Adl 1983;El-Serafy 1999;Gadallah et al 2017); Rhopalosiphum padi (L.) (Ghanim & El-Adl 1983;El-Serafy 1999;Starý et al 2000;Uysal et al 2004;Rakhshani et al 2008aRakhshani et al , 2008bChaouche & Laamari 2015), Schizaphis graminum (Rondani) (Ghanim & El-Adl 1983;El-Serafy 1999;Rakhshani et al 2008aRakhshani et al , 2008b; Sitobion avenae (Fabricius) (Ghanim & El-Adl 1983;Darvish-Mojeni 1994;El-Serafy 1999;Starý et al 2000;Rakhshani et al 2008aRakhshani et al , 2008bMossadegh et al 2011;Gadallah et al 2017)…”
Section: Host Recordsmentioning
confidence: 99%
“…;Chaouche & Laamari 2015;Ayadi et al 2017); Aphis pomi De Geer, Aphis potentillae Nevsky, Aphis punicae (Passerini) and Aphis solanella Theobald(Ayadi et al 2017); Aphis spiraecola Patch (Labdaoui & Guenaoui 2018); Brachycaudus cardui (L.) and Brachycaudus helichrysi (Kaltenbach); Diuraphis noxia (Kurdjumov)(Laamari et al 2016); Brevicoryne brassicae (L.)(Uysal et al 2004); Dysaphis foeniculus (Theobald)(Chaouche & Laamari …”
unclassified
See 1 more Smart Citation